Electricity Capital and Energy Poverty - Baker, Lucy H.; Cao, Umberto; Chipango, Ellen Fungisai; Fathoni, Hilman Syahri; Munro, Paul G.; Samarakoon, Shanil (Springer Nature, 2025)
This open access book explores the rise of new forms of electricity capitalism, examining how evolving energy systems shape energy consumption and access in five different case studies from the global South. Structured in seven chapters, it begins with a clear theoretical and conceptual foundation and is followed by five compelling case studies, grounded in research insights from Zimbabwe, Mexico, Uganda, Indonesia, and Vanuatu. The book concludes with a synthesis of these findings, paving the way for future discussions on energy poverty in the context of electricity capitalism in the Global South.